2005
DOI: 10.1582/leukos.02.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Visual, Biological and Emotional Aspects of Lighting: Recent New Findings and their Meaning for Lighting Practice

Abstract: Recent research in photobiology has revealed links between light and human health that are likely to have a significant effect on lighting practice. These effects should begin to be incorporated into lighting design practice and lighting recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 4 publications
0
10
0
4
Order By: Relevance
“…In the last decades researches demonstrated that light produce effects not only on the visual system, but also on human physiology and behaviour (see van Bommel 2004 for a review) [5]: these discoveries imposed to define new lighting criteria [6] and the principles of healthy lighting (CIE 158:2004; CIE 218:2016 ) [7], [8] were included in the concept of lighting quality. The luminous environment produces additional effect to vision, depending in particular on the light reaching the eyes: these non-visual effects are related mainly to the light features, such as spectral composition and intensity, and partially also to the environmental features that interact with the luminous beam incident on the eye, like colours and roughness of materials: even if these characteristics of materials are more relevant for the visual system, they can also partially impact on the non-visual process modifying through reflections the spectral composition of the light [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades researches demonstrated that light produce effects not only on the visual system, but also on human physiology and behaviour (see van Bommel 2004 for a review) [5]: these discoveries imposed to define new lighting criteria [6] and the principles of healthy lighting (CIE 158:2004; CIE 218:2016 ) [7], [8] were included in the concept of lighting quality. The luminous environment produces additional effect to vision, depending in particular on the light reaching the eyes: these non-visual effects are related mainly to the light features, such as spectral composition and intensity, and partially also to the environmental features that interact with the luminous beam incident on the eye, like colours and roughness of materials: even if these characteristics of materials are more relevant for the visual system, they can also partially impact on the non-visual process modifying through reflections the spectral composition of the light [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…Недавні медикобіологічні дослідження показали, що світло крім зорових функцій спричиняє на організм людини незоровий біологічний та психологічний вплив. Це означає, що хороше освітлення позитивно впливає на здоров'я, благополуччя, бадьорість і навіть на якість сну [1,2,3,4,5]. Дослідження впливу освітлення перед сном виявило, що в першій половині періоду сну лампи з підвищеною корельованою колірною температурою (далі -ССТ), знижують глибину сну сильніше ніж лампи з більш низькою ССТ [6].…”
Section: постановка проблемиunclassified
“…Тоді як максимум зорової чутливості для денного зору відповідає жовто-зеленій області спектра, максимум біологічної чутливості припадає на синю область. Такі властивості важливі для створення за рахунок змінення колірності від холоднобілої до тепло-білої біологічно активного або біологічно неактивного (розслаблюючого) освітлення [1]. Рядом досліджень підтверджено що короткохвильове світло в порівнянні з більшими довжинами хвиль ефективніше викликає фазовий зсув циркадної системи та пригнічення секреції мелатоніну, підвищує почуття бадьорості, підвищує частоту серцевих скорочень, температури тіла та експресію генів біологічного годинника [3].…”
Section: аналіз стану проблемиunclassified
See 1 more Smart Citation
“…Today, the role played by daylight on the state of mind, on physiology, and on the well-being of human beings seems to be certain, especially after the discoveries presented in [11,12]. These studies [13,14] demonstrate the role of biological lighting, as well as its effects on the circadian system and productivity.…”
Section: Introductionmentioning
confidence: 99%